Representasi Nilai Pendidikan Islam Sabar, Niat, dan Ikhlas dalam Novel Hati Suhita: Perspektif Imam Al-Ghazali - Syafinatun Najah; Irwan Ahmad Akbar; Hilyah Ashoumi (Lembaga Yasin AlSys, 2026)
Studies of the novel Hati Suhita have thus far focused primarily on themes of women, pesantren life, and Islamic character education, whereas analyses based on Imam Al-Ghazali’s educational thought, particularly concerning patience (sabr), intention (niyyah), and sincerity (ikhlas), remain limited. This study aims to analyze the representation of Islamic educational values in the form of patience, intention, and sincerity in Khilma Anis’s novel Hati Suhita from the perspective of Imam Al-Ghazali. The study employed a qualitative approach with a library research design. The primary data source was the novel Hati Suhita, while Ihya’ ‘Ulum al-Din was used as the principal theoretical foundation. The data were analyzed qualitatively by identifying and interpreting the representations of these three values in the novel. The findings indicate that Hati Suhita represents Islamic education as a process of moral and spiritual formation rather than merely the transmission of religious knowledge. Patience is portrayed through the ability to control one’s desires, manage emotions, and maintain steadfastness in facing life’s trials. Intention functions as an inner orientation that determines the moral and spiritual value of an action, while sincerity is represented as a process of purifying the heart from ego and worldly interests that leads individuals toward spiritual maturity. These three values are interconnected and form a comprehensive framework of Islamic education through character strengthening, self-discipline, and spiritual refinement in accordance with Imam Al-Ghazali’s thought. The findings of this study broaden the scope of Islamic education studies by affirming the role of literary works as a medium for internalizing moral and spiritual values. Practically, this study supports the use of literary works in learning to strengthen character education based on Islamic values and opens opportunities for developing studies of Islamic educational thought in other literary works.